The African-Norwegian case of supporting women towards knowledge production through doctoral studies - Hattingh, Annemarie (South African Journal of Higher Education, 2016)
This article pays attention to knowledge produced about a ‘networked’ support pathway towards a PhD. The network constituted an international collaboration through a project called Productive Learning Cultures (PLC) (2002-2011) between Norway and seven countries, developing or in transition, in sub-Saharan Africa which had both male and female students. However, this exploratory qualitative study describes how donor initiatives can be used to develop intellectual, emotional and funding support structures that take cognisance of the challenges women face during their PhD journeys. The article foregrounds the voices of women and accounts of their journey’s obstacles, reversals, breakdowns and yet, progression. In the findings the women describe the project design elements where they could benefit from international mindsets and supervision frameworks, while not having to leave their home countries for four years to pursue studies abroad. They also felt relieved gratitude that the project created a nurturing guilt-free space where motherhood and PhD work could co-exist which contributed towards emotional equilibrium which resulted in more effective PhD work. Keywords: doctoral learning, female student support, academic mothers, international cooperation, network, guilt-free study space.